2003
DOI: 10.1177/147323000303100305
|View full text |Cite
|
Sign up to set email alerts
|

The Histopathological Investigation of Pulpal Tissue following Heavy Orthopaedic Forces Produced by Rapid Maxillary Expansion

Abstract: This study aimed to investigate the effects of heavy orthopaedic forces, produced by rapid maxillary expansion, on pulpal tissue of pre-molar teeth. Teeth extracted as part of an orthodontic treatment plan, an average of 3 months, 6 months and 18 months after rapid maxillary expansion, were analysed using histopathological techniques. Control teeth were extracted, for orthodontic reasons, before any force treatment. Non-parametric tests were used to compare the results from the three treatment groups and one c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
25
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 14 publications
(9 reference statements)
6
25
0
Order By: Relevance
“…Kayhan et al 25 and Taspinar et al 26 suggested that repeated measurements of PBF at different stages of force application for evaluation of pulp hemodynamics were better than a single observation during force application. LDF can repeatedly measure PBF of the same tooth without causing damage to the pulp.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Kayhan et al 25 and Taspinar et al 26 suggested that repeated measurements of PBF at different stages of force application for evaluation of pulp hemodynamics were better than a single observation during force application. LDF can repeatedly measure PBF of the same tooth without causing damage to the pulp.…”
Section: Discussionmentioning
confidence: 99%
“…These histologic studies show inflammatory changes in the pulp tissue after orthopedic force application. 25,26 Both described areas of the vessels that were increased because of the inflammatory process.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations